Comparison of pulse glow discharge‐ion mobility spectrometry and liquid chromatography with tandem mass spectrometry based on multiplug filtration cleanup for the analysis of tricaine mesylate residues in fish and water. Issue 18 (25th August 2016) - Zou, Nan; Chen, Ronghua; Qin, Yuhong; Song, Shuangyu; Tang, Xinglin; Pan, Canping
Abstract : Analytical methods based on multiplug filtration cleanup coupled with pulse glow discharge‐ion mobility spectrometry and liquid chromatography tandem mass spectrometry were developed for the analysis of tricaine mesylate residue in fish and fish‐raising water samples. A silica fiber holder and an appropriate new interface were designed to make the direct introduction of the fiber into the pulse glow discharge‐ion mobility spectrometry introduction mechanism. The multiplug filtration cleanup method with adsorption mixtures was optimized for the determination of tricaine mesylate in fish samples. Good linear relationships were obtained by the two methods. For fish samples, limits of detection were 6 and 0.6 μg/kg by ion mobility spectrometry and liquid chromatography with tandem mass spectrometry, respectively. The matrix effect of the established liquid chromatography tandem mass spectrometry method was negligible for fish samples but that of the ion mobility spectrometry method was not. The two methods were compared. The ion mobility spectrometry system could be used a rapid screening tool on site with the advantage of rapidity, simplicity, and portability, and the liquid chromatography tandem mass spectrometry system could be used for validation in laboratory conditions with the advantage of lower limit of detection, stability, and precision.